Incidence and Associated Factors of Laryngospasm among Pediatric Patients Who Underwent Surgery under General Anesthesia, in University of Gondar Compressive Specialized Hospital, Northwest Ethiopia, 2019: A Cross-Sectional Study - Wubie Birlie Chekol; Debas Yaregal Melesse (Anesthesiology Research and Practice)
Introduction. Laryngospasm is a glottis closure due to reflex constriction of the laryngeal muscles. It can occur at any phase of the anesthetic. Different studies have been done previously with various results and indicative values which initiated us to do this research. This study aimed to assess the incidence and associated factors of laryngospasm among pediatric patients who underwent surgery under general anesthesia (GA). Methods. Institution-based, cross-sectional study was conducted on pediatric patients from February to August, 2019, in University of Gondar Comprehensive Specialized Hospital (UOGCSH). Data were entered and analyzed with SPSS version 20. Variables with P value less than <0.2 in bivariate analysis were fitted into the multivariable logistic regression analysis to identify factors associated with laryngospasm. Both crude and adjusted odds ratio with 95% CI were calculated to show strength of association. In multivariable analysis, P value of <0.05 was considered as statistically significant. Results. The incidence of laryngospasm among pediatric patients who underwent surgery under GA was 57 (18.4%). Of this, 34 (59.6%), 12 (21.1%), and 11 (19.3%) happened during emergence, maintenance, and induction phases of GA, respectively. In multivariable analysis, airway anomalies (AOR: 14.64, 95% CI: 1.71, 125.04), secretion (AOR: 2.45, 95% CI: 1.19, 5.06), attempts of airway devices (AOR: 2.47, 95% CI: 1.16, 5.22), upper respiratory tract infection (AOR: 2.91, 95% CI: 1.008, 8.41), and inadequate depth of anesthesia (AOR: 7.92, 95% CI: 2.7, 23.22) were significantly associated with incidence of laryngospasm. Conclusions. Laryngospasm can occur at any phase of the anesthetic. At UOGCSH, the overall rate of laryngospasm was 18.4%, with the vast majority of episodes occurring on emergence. Inadequate depth of anesthesia, URTI, airway anomalies, multiple attempts of airway devices, and oropharyngeal secretion were predictors of laryngospasm. So, added vigilance is needed in patients with URTI, airway anomalies, or those who require multiple attempts at airway device insertion. Prompt clearing of airway secretions and adequate depth of anesthesia may help to prevent laryngospasm. Since the majority of our patients received an IV induction, endotracheal intubation, and maintenance with halothane, caution must be taken in extrapolating these results to other patient populations.